PECULIARITIES OF DATA LOGGING AND INFLUENCE OF APPLICATION TYPE ON THE CHOICE OF LOGGING METHODOLOGY - KAPITANETS, Stepan; RADELCHUK, Galina (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Software is not perfect and may contain bugs that cannot be detected by tests, or that will manifest themselves only over time. Sometimes problems can occur even in the code of third-party libraries or services that are used in the software system. To improve the reliability of software systems and timely detection of problems, data logging is used. Logging is a very important aspect of software development. By studying application logs, software developers can detect anomalies and errors in software systems, find the cause and provide an update or patch with fixes. Nevertheless, despite the importance of data logging practice, in most cases this process is chaotic. Developers write logging code solely based on their own considerations or neglect it altogether. This study points to the need to improve the state of research on data logging practices. For example, more efforts should be made to define what exactly to log, to generate logging data in a clear way and from the developer’s point of view with enough information to recreate the events even without having to run the application. This article describes ways in which this can be achieved. This research aims to establish a comprehensive understanding of the state of the art in data logging research with an emphasis on identifying possible problems and gaps that will further shed light on potential future research directions. This paper describes a study that focused on logging strategies used on real projects of different types. It investigated logging methods for desktop and web applications, and proposed improvements to the logging methodology that make it more flexible and convenient for software development teams regardless of the types of applications being developed.